The use of circularity index of soil aggregates to differentiate degraded stratate - Carvalho, Marcela Merides; Fengler, Felipe Hashimoto; Peche Filho, Afonso (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2020)
Among the difficulties encountered in the management of degraded areas is the characterization of the different stratum within the same area. These strata possibly need different recovery actions, compatible with the form of degradation. Based on this premise, the work proposes an initial stratification based on the visual perception of the different forms of degradation occurring in the local landscape. In this way, a better understanding of the landscape and the sampling needs are sought in order to confirm the differences. Thus, the objective of the work was to identify the different stratum in a degraded area, using soil sampling for the purposes of aggregation analysis and determination of the circularity index of the different soil aggregates. The experiment was carried out in a degraded area at the Agronomic Institute (CEA-IAC), in the city of Jundiaí - SP. The site was stratified into five degradation environments and for each of them four samples were taken for the purpose of analyzing the aggregation state. After sieving the soil sample, a sub-sample of aggregates retained in the 4 mm sieve was removed to determine the circularity index. Using 40 samples per stratum, descriptive statistical measures and the frequency histogram were obtained. The results showed that through the analysis of aggregates, the statistical processing of the circularity index and the making of frequency histograms, we can establish reliable criteria for differentiating strata in degraded areas. Thus, we can conclude that the procedures used have the potential to analyze and differentiate environments with levels of complex degradation.